Evidence Mapping Based on Systematic Reviews of Repetitive Transcranial Magnetic Stimulation on the Motor Cortex for Neuropathic Pain - Zang, Yaning; Zhang, Yongni; Lai, Xigui; Yang, Yujie; Guo, Jiabao; Gu, Shanshan; Zhu, Yi (Frontiers in Human Neuroscience, 2022)
Background and Objective: There is a vast published literature proposing repetitive transcranial magnetic stimulation (rTMS) technology on the motor cortex (M1) for the treatment of neuropathic pain (NP). Systematic reviews (SRs) tend to a specific problem and do not provide a comprehensive overview of research area. This study aimed to summarize and analyze the evidence of rTMS on the M1 for NP through a new synthesis method --evidence mapping. Methods: Searches were conducted in PubMed, EMBASE, Epistemonikos, and The Cochrane Library to identify the studies that summarized the effectiveness of rTMS for NP. The study type was restricted to SRs with or without meta-analysis. All literature published before January 23, 2021 was included. Two reviewers independently screened the literature, assessed the methodological quality, and extracted the data. The methodological quality of the included SRs was assessed by using the A Measurement Tool to Assess Systematic Reviews (AMSTAR-2). Data was extracted according to a defined population-intervention-comparison-outcome (PICO) framework from primary studies that included SRs. The same PICO was categorized into PICOs according to interventions [frequency, number of sessions (short: 1-5 sessions, medium: 5-10 sessions, long: > 10 sessions)], and comparison. The evidence mapping was presented in tables and a bubble plot. Results: A total of 40 SRs met the eligibility criteria. After duplicate primary studies were removed, these reviews included 79 primary studies that met the scope of the evidence mapping. According to the AMSTAR-2 assessment, the quality of the included SRs was critically low, overall. Of which, 37 SRs scored “critically low” in terms of methodological quality, 1 SR scored “low,” 1 SR scored “moderate,” and 1 SR scored “high.” Conclusions: Evidence mapping which is a useful methodology to provide a comprehensive and reliable overview of studies on rTMS for NP. This evidence mapping also shows further investigations are necessary in order to highlight the optimal stimulation protocols and standardize all parameters to fill the evidence gaps of rTMS. Given that the methodological quality of most included SRs was “critically low,” further investigations are advised to improve the methodological quality and the reporting process of SRs.